Social and psychological bases of ideology and system justification - Jost, John T.; Kay, Aaron C.; Thorisdottir, Hulda (Oxford : Oxford University Press, 2009)
This new volume on 'Social and Psychological Bases of Ideology and System Justification' brings together several of the most prominent social and political psychologists who are responsible for the resurgence of interest in the study of ideology, broadly defined.
Description based on print version record.
Includes bibliographical references and index.
Keywords: United States -- Politics and government -- 2001-2009.; Ideology -- Political aspects -- United States; Political psychology; Religion and politics -- United States; Political culture -- United States; Right and left (Political science); Public opinion -- United States